2016
DOI: 10.1007/s00415-016-8185-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of botulinum toxin treatment on quality of life in patients with isolated lingual dystonia and oromandibular dystonia affecting the tongue

Abstract: The purpose of this study was to investigate the impact of botulinum toxin (BoNT) treatment on the quality of life (QoL) for patients with prominent lingual dystonia (LD) using a disease-specific questionnaire, the oromandibular dystonia questionnaire-25 (OMDQ-25). This is a prospective, observational study of a cohort of 30 patients treated with BoNT injections for LD, with or without concurrent jaw dystonia. Primary efficacy outcome was the absolute difference between total OMDQ-25 baseline score and total O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…Little systematic information has been published on the course of OMD over time and the treatment effect, but in general, it seems that BoNT treatment is well tolerated and improves function and quality of life . However, to facilitate research and clinical practice, precise tools to rate improvement or deterioration are important to assess disease state and outcome after treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Little systematic information has been published on the course of OMD over time and the treatment effect, but in general, it seems that BoNT treatment is well tolerated and improves function and quality of life . However, to facilitate research and clinical practice, precise tools to rate improvement or deterioration are important to assess disease state and outcome after treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Natasi et al used the OMDQ-25 to investigate the impact of BoNT-A injections on QoL for individuals with predominantly lingual dystonia. 49 Overall, this study reported that BoNT-A injections can result in a consistent and measureable improvement in QoL for individuals with predominantly lingual dystonia. Merz and colleagues also reported improvements across all subscales of the OMDQ-25 following BoNT-A injections, with the "cosmetic" subscale demonstrating the greatest improvement following injections with BoNT-A.…”
Section: Management Of Psychosocial Issuesmentioning
confidence: 59%
“…The majority of these published studies have evaluated health-related QoL before and after botulinum toxin injections to determine if this medical intervention is effective for improving QoL. 1,48,49 Most of these studies have used the Glasgow Benefit Inventory (GBI) to measure the change in a patient's health produced by an intervention. The GBI is an 18-item questionnaire, divided into three domains (general subscore, social support subscore, physical health subscore).…”
Section: Management Of Psychosocial Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that QoL improves with toxin treatment of OMD [13,14]. The OMDQ-25 is a validated instrument that has been shown by us and others to demonstrate response [12,34].…”
Section: Discussionmentioning
confidence: 99%